2016
DOI: 10.1177/1476718x15609390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of academic and non-academic instructional approaches on preschool English language learners’ classroom engagement and English language development

Abstract: This research compared the relative impact of different preschool activities on the development of bilingual students' English-language skills. The study investigated whether bilingual preschool children would engage more, and use more of their second language (English), during free-play (non-academic) versus teacher-structured (academic) activities. The researcher utilized both quantitative and qualitative research approaches; data sources included 285 preschool observations made in three classrooms in Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
8
0
6
Order By: Relevance
“…The authors assert that both types of activities have the potential to provide learning opportunities for children with disabilities, but that they require skilled scaffolding from teachers to help the children. Markova (2017) found remarkably similar results for ELL children in classroom settings. Children learning English were dramatically more engaged during free play than during teacher-directed activities.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The authors assert that both types of activities have the potential to provide learning opportunities for children with disabilities, but that they require skilled scaffolding from teachers to help the children. Markova (2017) found remarkably similar results for ELL children in classroom settings. Children learning English were dramatically more engaged during free play than during teacher-directed activities.…”
Section: Introductionsupporting
confidence: 56%
“…Multiple studies have emphasized the importance of adult scaffolding and assistance for both children who are ELL (e.g., Markova, 2017) and children with special needs. Mills et al (2014) found that to enable young children with language disabilities to interact effectively with peers, adults must help structure the play situation.…”
Section: Introductionmentioning
confidence: 99%
“…These experiences will likely be important for these PSTs as they further learn about second-language acquisition processes and their impact on student learning. Therefore, setting the stage/environment for these types of interactions is an important component of relationship-building, which is viewed as a valuable context for oral language development (Magruder et al, 2013;Markova, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Explicit, appropriate, language instruction and assessment are components that characterize programs providing the best outcomes for DLLs. "Child-centered" free play opportunities offer DLLs significantly higher levels of engagement and language rich interactions than teacher-directed academic activities (Markova, 2017).…”
Section: Effective Practices For Teaching Dllsmentioning
confidence: 99%
“…In this regard, Mehana (2018, p. 94) concludes from her research on state kindergarten teachers that "a prevailing view was that teaching academic skills in a structured environment would help children prepare for Grade 1." However, research elsewhere has found that free play time affords more opportunities for second language development of young learners than teacher-directed activities (Markova 2016;Schwartz and Deeb 2018).…”
Section: Curricular Choicementioning
confidence: 99%